A Study on Impact of Customer Centric Marketing on Customer Retention in Nepalese Life Insurance - Rawal, Soniya; Bhatt, Om Prakash (Far Western Review, 2025)
Customer-centric marketing is a crucial factor in determining the survival and success of life insurers, particularly in competitive markets like Nepal. This study investigates the role of account control, trust benevolence, perceived risk, and interactive communication in enhancing customer retention within Nepalese life insurance. The study employs a qualitative survey methodology, using a non-probability snowball sampling approach across Kathmandu Valley and beyond. It collects data from 178 respondents, yielding 152 valid responses. Reliability testing confirms strong internal consistency with Cronbach’s alpha exceeding 0.7. The analysis is conducted using descriptive statistics and ordinal logistic regression. All variables are statistically significant at a 95% confidence level, demonstrating their influence on customer retention. Account control is identified as the most impactful factor, followed by interactive communication, while trust benevolence has the least effect. Customer-centric strategies play a vital role in fostering loyalty in Nepalese life insurance. Strengthening account control mechanisms and improving communication channels can drive long-term engagement and policyholder trust. Practical implications for insurers in Nepal include the need to invest in digital platforms that allow policyholders to manage their accounts independently, train staff in responsive and personalized communication, and develop targeted strategies to reduce perceived risk. By prioritizing these areas, insurers can build stronger relationships, reduce churn, and improve overall customer satisfaction.